MiR‐590‐3p regulates proliferation, migration and collagen synthesis of cardiac fibroblast by targeting ZEB1. Issue 1 (1st November 2019) - Yuan, Xiaolong; Pan, Jinchun; Wen, Lijuan; Gong, Baoyong; Li, Jiaqi; Gao, Hongbin; Tan, Weijiang; Liang, Shi; Zhang, Hao; Wang, Xilong
Abstract: Previous studies have implicated the attractive and promising role of miR‐590‐3p to restore the cardiac function following myocardial infarction (MI). However, the molecular mechanisms for how miR‐590‐3p involves in cardiac fibrosis remain largely unexplored. Using human cardiac fibroblasts (HCFs) as the cellular model, luciferase report assay, mutation, EdU assay and transwell migration assay were applied to investigate the biological effects of miR‐590‐3p on the proliferation, differentiation, migration and collagen synthesis of cardiac fibroblasts. We found that miR‐590‐3p significantly suppressed cell proliferation and migration of HCFs. The mRNA and protein expression levels of α‐SMA, Col1A1 and Col3A were significantly decreased by miR‐590‐3p. Moreover, miR‐590‐3p directly targeted at the 3'UTR of ZEB1 to repress the translation of ZEB1 . Interfering with the expression of ZEB1 significantly decreased the cell proliferation, migration activity, mRNA and protein expressions of α‐SMA, Col1A1 and Col3A . Furthermore, the expressions of miR‐590‐3p and ZEB1 were identified in infarct area of MI model in pigs. Collectively, miR‐590‐3p suppresses the cell proliferation, differentiation, migration and collagen synthesis of cardiac fibroblasts by targeting ZEB1 . These works will provide useful biological information for future studies on potential roles of miR‐590‐3p as the therapeutic target to recover cardiac function following MI.